THE INFLUENCE OF E-WOM ON ONLINE PURCHASE INTENTION MEDIATED BY BRAND IMAGE (STUDY AT SAMSAM MEREKAK RESTAURANT) - Stefanus Ryan Dwi Kurnia; Gede Suparna (Adisam Publisher, 2026)
This study aims to analyze the effect of Electronic Word of Mouth (E-WOM) on online purchase intention, with brand image as a mediating variable, in the context of Samsam Merekak Restaurant. Online purchase intention represents a crucial stage in the digital buying process, reflecting consumers’ considerations before deciding to make a purchase through online platforms. Understanding the factors influencing online purchase intention is essential, particularly for culinary businesses that increasingly rely on digital marketing and consumer behavior shaped by online recommendations. This research employs a quantitative method with an associative approach. The sample was determined using a non-probability sampling technique with purposive sampling, resulting in an adequate number of respondents for analysis. Data were collected through an online questionnaire. The analytical techniques used include path analysis and the Sobel test, conducted after all prerequisite assumption tests were fulfilled. The findings indicate that E-WOM has a positive and significant effect on brand image, and E-WOM also positively and significantly influences online purchase intention. Furthermore, brand image positively and significantly affects online purchase intention, demonstrating its crucial role in shaping consumers’ digital buying intentions. Lastly, the results confirm that brand image partially mediates the relationship between E-WOM and online purchase intention. The practical implications of this study suggest that Samsam Merekak should strengthen its E-WOM strategies by enhancing the quality of customer reviews, increasing engagement on social media, and managing customer testimonials more effectively. Additionally, reinforcing brand image through consistent brand identity, highlighting the restaurant’s uniqueness, and improving service quality is essential to boost online purchase intention and maintain competitiveness in the increasingly dynamic digital culinary industry.